2001
DOI: 10.2337/diabetes.50.8.1844
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease

Abstract: Insulin sensitivity (euglycemic clamp, insulin infusion rate: 40 mU ⅐ m ؊2 ⅐ min ؊1) was studied in 30 subjects with biopsy-proven nonalcoholic fatty liver disease (NAFLD), normal glucose tolerance, and a BMI <30 kg/m 2 . Of those 30 subjects, 9 had pure fatty liver and 21 had evidence of steatohepatitis. In addition, 10 patients with type 2 diabetes under good metabolic control and 10 healthy subjects were studied. Most NAFLD patients had central fat accumulation, increased triglycerides and uric acid, and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

58
1,489
16
46

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,157 publications
(1,609 citation statements)
references
References 54 publications
58
1,489
16
46
Order By: Relevance
“…NAFLD is commonly associated with components of metabolic syndrome2 and is an independent risk factor for cardiovascular disease 3, 4…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD is commonly associated with components of metabolic syndrome2 and is an independent risk factor for cardiovascular disease 3, 4…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there is firm evidence that obesity is associated with nonalcoholic fatty liver diseases (NAFLD). 4 Therefore, without considering the effect of higher fat mass, interpreting a harmful effect of decreased percent muscle mass on NAFLD as a result of decreased muscle mass seems to be inadequate.…”
Section: Replymentioning
confidence: 99%
“…In the Korean Longitudinal Study on Health and Aging, Lim et al defined sarcopenia using ASM/ height 2 or ASM/Wt of <1 SD below the sex-specific mean for young adults. 4 To examine the prevalence of SO, they also defined obesity as a visceral fat area 100 cm 2 . They concluded that subjects with SO defined by ASM/Wt were more insulin resistant and had a higher risk for metabolic syndrome than simply obese subjects.…”
Section: Replymentioning
confidence: 99%
See 1 more Smart Citation
“…The association between NAFLD and insulin resistance is even greater than that observed in alcoholic CLD, and some authors consider NAFLD as the hepatic manifestation of the metabolic syndrome [31]. However, the exact role of this metabolic impairment remains to be defined, and insulin resistance probably plays a bi-directional role in this type of liver disease.…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%